Nascent Glycoproteome Reveals That N-Linked Glycosylation Inhibitor-1 Suppresses Expression of Glycosylated Lysosome-Associated Membrane Protein-2 - Cao, Xinyi; Meng, Peiyi; Shao, Yuyin; Yan, Guoquan; Yao, Jun; Zhou, Xinwen; Liu, Chao; Zhang, Lei; Shu, Hong; Lu, Haojie (Frontiers in Molecular Biosciences, 2022)
Glycosylation inhibition has great potential in cancer treatment. However, the corresponding cellular response, protein expression and glycosylation changes remain unclear. As a cell-permeable small-molecule inhibitor with reduced cellular toxicity, N-linked glycosylation inhibitor-1 (NGI-1) has become a great approach to regulate glycosylation in mammalian cells. Here for the first time, we applied a nascent proteomic method to investigate the effect of NGI-1 in hepatocellular carcinoma (HCC) cell line. Besides, hydrophilic interaction liquid chromatography (HILIC) was adopted for the enrichment of glycosylated peptides. Glycoproteomic analysis revealed the abundance of glycopeptides from LAMP2, NICA, and CEIP2 was significantly changed during NGI-1 treatment. Moreover, the alterations of LAMP2 site-specific intact N-glycopeptides were comprehensively assessed. NGI-1 treatment also led to the inhibition of Cathepsin D maturation and the induction of autophagy. In summary, we provided evidence that NGI-1 repressed the expression of glycosylated LAMP2 accompanied with the occurrence of lysosomal defects and autophagy.